Prevalence of Strongyle Infection and Associated Risk Factors in Horses and Donkeys in and around Mekelle City, Northern Part of Ethiopia - Wossene Negash; Yosef Erdachew; Teshager Dubie (Veterinary Medicine International)
Background. In Ethiopia, equines serve in traction power, carting, recreation, festival packing, riding, transportation, and other activities since time immemorial. Strongyles are common equine health problems in Ethiopia though research based data on equine strongyles are limited particularly in the study areas, in and around Mekelle city. Therefore, the present study was intended to estimate the prevalence of common equine strongyles in and around Mekelle city from November 2018 to April 2019 and to assess risk factors associated with infection of strongyle parasites as well. Cross sectional design was used in this study, and the study population consisted of both donkeys and horses of all age and both sex groups. From randomly selected horses and donkeys, approximately 25 grams of faecal samples was drawn with gloved hands from rectum of study equines, labeled, and transported to laboratory for coprological examination. Flotation technique was employed to separate parasitic eggs from faeces, followed by microscopic examination for identification of strongyle eggs based on morphology. Pearson’s chi-square (χ2) was carried out to determine association between risk factors and parasitic infection. Moreover, both bivariate and multivariate logistic regression analyses were computed to assess the strength of association of those risk factors at 95% CI and P<0.05. Result. Out of 384 samples collected, 204 were found to be positive for strongyles with an overall prevalence of 53.13%. Prevalence of strongyle species in equines was also estimated to be 53% and 53.3% for donkeys and horses, respectively. Accordingly, of the six risk factors considered, only three factors (age, management type, and body condition scores) were found to influence the occurrence of strongyle infection and to be statistically significant as well. Conclusion. The higher prevalence of equine strongyles in the present study might be suggestive of urgent and coordinated actions to be in place.